TCR-induced FOXP3 expression by CD8+ T cells impairs their anti-tumor activity. (1st March 2022) - Lozano, Teresa; Conde, Enrique; Martín-Otal, Celia; Navarro, Flor; Lasarte-Cia, Aritz; Nasrallah, Rabab; Alignani, Diego; Gorraiz, Marta; Sarobe, Pablo; Romero, Juan P.; Vilas, Amaia; Roychoudhuri, Rahul; et al.
Abstract: Adoptive cell transfer therapy using CD8 + T lymphocytes showed promising results eradicating metastatic malignancies. However, several regulatory mechanisms limit its efficacy. We studied the role of the expression of the transcription factor FOXP3 on CD8 + T cell function and anti-tumor immunity. Here we show that suboptimal T cell receptor stimulation of CD8 + T cells upregulates FOXP3 in vitro. Similarly, CD8 T cells transferred into tumor-bearing mice upregulate FOXP3 in vivo . Cell-intrinsic loss of FOXP3 by CD8 + T cells resulted in improved functionality after TCR stimulation and better antitumor responses in vivo . Inhibition of the FOXP3/NFAT interaction likewise improved CD8 + T cell functionality. Transcriptomic analysis of cells after TCR stimulation revealed an enrichment of genes implicated in the response to IFN-γ, IFN-α, inflammatory response, IL-6/JAK/STAT, G2M checkpoint and IL-2/STAT signaling in FOXP3-deficient CD8 + T cells with respect to FOXP3-wt CD8 + T cells. Our results suggest that transient expression of FOXP3 by CD8 + T cells in the tumor microenvironment restrains their anti-tumor activity, with clear implications for improving T cell responses during immunotherapy. Highlights: FOXP3 expression is induced after suboptimal TCR stimulation in CD8 + T cells. Inhibition of NFAT/FOXP3 interaction or FOXP3 silencing in activated CD8 + T cells improves T cell proliferation, cytokine production, lytic activity and antitumor efficacy. Foxp3 expression in CD8 + T cells changes the CD8 T cell transcriptomic profile determining the fate of the lymphocyte. FOXP3 expression in CD8 + T cells could act as a mechanism to quickly turn off the effector T cells infiltrating the tumor.